OBSERVATION OF HARD SCATTERING IN PHOTOPRODUCTION AT HERA - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Sugano, K; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayed, R; Barbagli, G; et al. (1992)
We report a study of electron proton collisions at very low Q2, corresponding to virtual photoproduction at centre of mass energies in the range 100-295 GeV. The distribution in transverse energy of the observed hadrons is much harder than can be explained by soft processes. Some of the events show back-to-back two-jet production at the rate and with the characteristics expected from hard two-body scattering. A subset of the two-jet events have energy in the electron direction consistent with that expected from the photon remnant in resolved photon processes.